Therapeutic targeting of mineralocorticoid receptors in pulmonary hypertension: Insights from basic research - Mamazhakypov, Argen; Lother, Achim (Frontiers in Cardiovascular Medicine, 2023)
Pulmonary hypertension (PH) is characterized by pulmonary vascular remodeling and associated with adverse outcomes. In patients with PH, plasma aldosterone levels are elevated, suggesting that aldosterone and its receptor, the mineralocorticoid receptor (MR), play an important role in the pathophysiology of PH. The MR plays a crucial role in adverse cardiac remodeling in left heart failure. A series of experimental studies from the past few years indicate that MR activation promotes adverse cellular processes that lead to pulmonary vascular remodeling, including endothelial cell apoptosis, smooth muscle cell proliferation, pulmonary vascular fibrosis, and inflammation. Accordingly, in vivo studies have demonstrated that pharmacological inhibition or cell-specific deletion of the MR can prevent disease progression and partially reverse established PH phenotypes. In this review, we summarize recent advances in MR signaling in pulmonary vascular remodeling based on preclinical research and discuss the potential, but also the challenges, in bringing MRA into clinical application.